2015
DOI: 10.2166/wpt.2015.100
|View full text |Cite
|
Sign up to set email alerts
|

Fouling mechanisms and reduced chemical potential of ceramic membranes combined with ozone

Abstract: Combining ceramic membranes with ozonation and allowing ozone residual to contact the membrane surface is well known to control fouling, allowing for higher membrane fluxes. This means that the more robust, longer lasting and higher integrity ceramic material can potentially be used in water recycling in a cost competitive way. This paper presents additional results from a previously reported ozonation/ceramic membrane trial in Melbourne, Australia. The results assisted in understanding the cause of the high f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 4 publications
2
14
0
Order By: Relevance
“…In considering ceramic membranes, high flux is important to offset their higher material cost but must be operated in a specific way to achieve this, which would impact the downstream RO plant operation. For example Dow and co-workers demonstrated that the sustainable ceramic microfiltration (CMF) membrane fluxes for treating clarified wastewater increased 2-3 fold in response to dosing with the common coagulant polyaluminium chloride (PACl) [2,3]. Coagulation used prior to polymer membranes is already known to reduce fouling as well as to remove organic matter, particularly the large molecular weight (MW) components, being biopolymers and humic substances [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In considering ceramic membranes, high flux is important to offset their higher material cost but must be operated in a specific way to achieve this, which would impact the downstream RO plant operation. For example Dow and co-workers demonstrated that the sustainable ceramic microfiltration (CMF) membrane fluxes for treating clarified wastewater increased 2-3 fold in response to dosing with the common coagulant polyaluminium chloride (PACl) [2,3]. Coagulation used prior to polymer membranes is already known to reduce fouling as well as to remove organic matter, particularly the large molecular weight (MW) components, being biopolymers and humic substances [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…[7] concluded that coagulation treatment reduced organic fouling by removal of these largersized materials. Further, ozone used in conjunction with coagulation and ceramic membranes was observed to work together to provide >4-fold sustainable flux increases for ceramic membranes [2]. Oxidation processes such as ozonation, and ultraviolet irradiation (UV), are commonly practised as the tertiary treatments to meet appropriate water quality in reclaimed water from secondary wastewater treatment plant (WWTP) effluents for disinfection purposes, odour treatment as well as the removal of colour caused by humic substances.…”
Section: Introductionmentioning
confidence: 99%
“…Ozonation, employing a strong oxidation effect of ozone on pathogen inactivation, bio-degradability improvement of organic matter, degradation of chemicals of concern (CoC), a lower chemical consumption associated with cleaning of the downstream ceramic micro-filtration (MF) and improved backwash efficiency [4,5]. 2.…”
Section: Major Operational Parameters and Verification Methods For Eacmentioning
confidence: 99%
“…Caustic cleaning to remove organic fouling is expected to be effective, where previous work on caustic cleaning of polyvinylidene fluoride (PVDF) MD membranes fouled with humic acid and calcium solutions was very effective [41]. The inability of sodium hypochlorite to further restore flux is surprising, as it is well known to clean both PVDF and ceramic membranes used in low pressure filtration [43,44]. The reasons may relate to the very different membrane chemistries (hydrophobic PTFE vs hydrophilic PVDF) where the attachment of the fouling materials to the membrane work by different mechanisms [52,53], or indeed the nature of textile processing materials and their resistance to chlorine degradation.…”
Section: Membrane Cleaningmentioning
confidence: 99%
“…pH 9) [42]. Sodium hypochlorite is also utilised in removing organic matter from filtration membranes [43,44] and may be suitable for MD. However experience on cleaning MD membranes after treatment of real textile wastewater is limited, and more work is needed to demonstrate effective cleaning for practical longer term operation.…”
Section: Introductionmentioning
confidence: 99%